Strategic human resources management : a systems approach - Bassett-Jones, Nigel (Routledge, 2023)
"This innovative text applies a systems theory perspective to strategic human resource management, drawing particularly on the Viable Systems Model and soft systems methodology. Readers are introduced to different ways of thinking about systems and shown how systems can interact, triggering changes in the competitive environment - and how HR systems can either facilitate or inhibit adaptation to these changes. Peppered with international examples throughout, this book considers key HR topics such as recruitment, reward, employment relations, culture, diversity and leadership, all through a systems lens. It shows how an understanding of system dynamics can help managers to recognise complexity, accept the inevitability of short-term systemic conflicts and anticipate the likely consequences. This text will be suitable for upper-level undergraduate, postgraduate and MBA students of strategic HRM, HRM and strategic management. It will also be thought-provoking for HR professionals looking to embrace a strategic role in their organizations"--